The limitations and possibilities of the didactic game Kallipolis: the governments’ game - Brinati Furtado, Daniela; da Silva Fortes, Fábio; Boechat Marcílio, Luca (Revista Archai, 2022)
The present article has as its object to present the elaboration and testing process of the project Kallipolis: the governments’ game. The project involves the development of a game,aiming at the illustration and creation of an environment where a student can discover and think with the reflections that Plato presents in the eighth book of the Republic. Inthelight of that,firstlyit is briefly explained the game’s theoretical basis and how it stems from the book VIII of Plato’s Republic. Subsequently,based on what has been observed in the testing process, the game’s limitations are considered along with its possible uses by asecondary school Philosophy teacher.